1978
DOI: 10.1002/1097-0142(197804)41:4<1399::aid-cncr2820410426>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of esophageal dysplasia by cytofluorometric analysis

Abstract: In order to grade objectively and characterize dysplastic and precancerous esophageal epithelium its DNA content was measured by cytofluorometric methods and compared to normal and cancerous esophageal epithelium. This yielded the following results. With transition of the esophageal epithelium from mild dysplasia to severe dysplasia and finally to in situ carcinoma, Feulgen-DNA values showed patterns characteristic of a tetraploid population. They lacked prominent peaks which were usually observed with invasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1978
1978
2005
2005

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Cytologic follow-up data from China (1975) indicated that 21 (26.6%) among 79 persons with cytologically severe dysplasia progressed to carcinoma and 26 (32.9%) remained more or less severe dysplasia. In our recent study on nuclear DNA con tent in squamous cells of the esophagus, histogram of moderate and severe dysplasia showed an intermediate pattern (Mukada et al 1978) between normal and that of carcinoma. These results disclosed a biological nature of dysplasia as a possible forerunner of carcinoma.…”
Section: Discussionmentioning
confidence: 83%
“…Cytologic follow-up data from China (1975) indicated that 21 (26.6%) among 79 persons with cytologically severe dysplasia progressed to carcinoma and 26 (32.9%) remained more or less severe dysplasia. In our recent study on nuclear DNA con tent in squamous cells of the esophagus, histogram of moderate and severe dysplasia showed an intermediate pattern (Mukada et al 1978) between normal and that of carcinoma. These results disclosed a biological nature of dysplasia as a possible forerunner of carcinoma.…”
Section: Discussionmentioning
confidence: 83%
“…In other words, they may show chronologically gradual transition toward distinct carcinoma as an extreme. This may be interpreted as a common feature of the preneoplastic lesions of the esophagus (Mukada et al 1978). In the pancreas, after the dysplastic lesion has reached its full development up to carcinoma (in situ), and has once gained aggressive nature, its atypical offsprings, papillary or nonpapillary, may develop into flank invasive pancreatic carcinoma, though the carcinoma may be occult at times (Figs.…”
Section: Resultsmentioning
confidence: 97%
“…To discuss these problems, the concept "dysplasia" may be helpful. We know some precancerous lesions in the human body as well exemplified by adenoma of the gastrointestinal tract, and dysplasia of the cervix and the esophagus (Mukada et al 1978). But the pancreas is quite different from these organs in that materials for morphological study must be collected during surgery often for advanced carcinoma, or from autopsy cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Esophageal dysplasia is frequently encountered in squamous cell carcinoma of the esophagus [1], and previous studies have suggested the significance of dysplasia as a precancerous lesion [2][3][4][5]. In a study, epithelial squamous dysplasias of the esophageal mucosa and subclinical carcinoma, respectively, were found in 67 (26.7%) and 6 (2.4%) of 251 autopsied cases of nonesophageal carcinoma [6], suggesting that epithelial squamous dysplasia could be a site of cancer development origin.…”
Section: Introductionmentioning
confidence: 94%